A daily diary study of emotion regulation as a moderator of negative affect‐binge eating associations. Issue 10 (2nd July 2022) - Mikhail, Megan E.; Fowler, Natasha; Burt, S. Alexandra; Neale, Michael C.; Keel, Pamela K.; Katzman, Debra K.; Klump, Kelly L.
Abstract: Background: While negative affect (NA) typically increases risk for binge eating, the ultimate impact of NA may depend on a person's ability to regulate their emotions. In this daily, longitudinal study, we examined whether emotion regulation (ER) modified the strength of NA‐dysregulated eating associations. Methods: Women ( N  = 311) from the Michigan State University Twin Registry first reported dimensional binge eating symptoms and broad ER difficulties (e.g., limited emotional awareness, difficulty controlling emotional impulses). Participants then rated use of adaptive (cognitive reappraisal, social sharing, situation modification, and acceptance) and maladaptive (rumination, expressive suppression, and self‐criticism) ER strategies, emotional eating (EE), objective binge eating (OBE), and NA once daily for 49 consecutive days. Results: There were several main effects of ER on binge‐eating pathology in both between‐person (i.e., comparing women who differed on average) and within‐person (i.e., examining fluctuations in variables day‐to‐day) analyses. Between‐person, greater broad ER difficulties, greater maladaptive strategy use, and lower adaptive strategy use were all associated with greater binge‐eating pathology. Within‐person, greater maladaptive strategy use was associated with greater odds of OBE on that day and on the following day. However, neither broad ER difficulties nor use of specific strategies moderated associations between NA and dysregulated eating in between‐ or within‐person analyses. Conclusions: While ER is independently associated with risk for dysregulated eating, it may not fully mitigate the impact of NA. Additional strategies (e.g., decreasing environmental stressors and increasing social support) may be needed to minimize NA and its impact on dysregulated eating. Public Significance: Negative affect (NA; e.g., sadness, guilt) increases dysregulated eating risk. Because NA is sometimes unavoidable, we examined whether emotion regulation (ER; i.e., how a person responds to their emotions) might impact whether NA leads to dysregulated eating. Although more effective ER was associated with less dysregulated eating overall, ER did not impact the association between NA and dysregulated eating. Other approaches may therefore be needed to mitigate NA‐dysregulated eating associations.